Komodifikasi Tari Sanghyang Dedari di Desa Bona, Kecamatan Blahbatuh, Kabupaten Gianyar, Provinsi Bali - Harsana, I Ketut Gede; Mancapara, I Gede Pasek (Sphatika: Jurnal Teologi, 2023)
Abstract This article examines and analyzes the Sanghyang Dedari Dance which has experienced commodification in Bona Village. As one of the sacred arts performed in a state of trance, at first the Sanghyang Dance was performed only for spiritual purposes, but now the Sanghyang Dance has experienced commodification in the era of globalization in line with the development of tourism and science and technology. The method used in this study is qualitative with a phenomenology approach. The results showed that the Sanghyang Dance in Bona Village was only the Sanghyang Dedari dance, this dance is still performed regularly from the past until now only at the Bona Village Temple, apart from that as a tourism need the Sanghyang dance is also staged in hotels as a dance performance. reconstructed with the presence of additional elements such as accompaniment of Kecak. Broadly speaking, there are similarities and differences in the Sanghyang dance as a sacred dance and as a performance dance. The similarities are that the dancers are selected according to the criteria of being pure and the clothes used are the same, while the difference lies in the preparation process until the dance is performed, the instruments used, the duration and the accompaniment. Keywords: Reconstruction, Sanghyang Dedari Dance, Commodification.